Climate variability and inter-provincial migration in South America, 1970–2011. (November 2016) - Thiede, Brian; Gray, Clark; Mueller, Valerie
Highlights: Extreme monthly temperatures have the most consistent effects on migration in the region. Much of the climate-related inter-province migration is directed toward urban areas. Climate effects on migration vary by country and historical climate conditions. Abstract: We examine the effect of climate variability on human migration in South America. Our analyses draw on over 21 million observations of adults aged 15–40 from 25 censuses conducted in eight South American countries. Addressing limitations associated with methodological diversity among prior studies, we apply a common analytic approach and uniform definitions of migration and climate across all countries. We estimate the effects of climate variability on migration overall and also investigate heterogeneity across sex, age, and socioeconomic groups, across countries, and across historical climate conditions. We also disaggregate migration by the rural/urban status of destination. We find that exposure to monthly temperature shocks has the most consistent effects on migration relative to monthly rainfall shocks and gradual changes in climate over multi-year periods. We also find evidence of heterogeneity across demographic groups and countries. Analyses that disaggregate migration by the rural/urban status of destination suggest that much of the climate-related migration is directed toward urban areas. Overall, our results underscore the complexity of environment-migration linkages and challenge simplistic narratives that envision a linear and monolithic migratory response to changing climates.